LMD-10. The role of immune checkpoint inhibitors in leptomeningeal disease: a systematic review. (9th August 2021) - Palmisciano, Paolo; Haider, Ali S; Nwagwu, Chibueze D; Wahood, Waseem; Sagoo, Navraj S; Yu, Kenny; Ene, Chibawane I; O'Brien, Barbara J; Cohen-Gadol, Aaron A; El Ahmadieh, Tarek Y
Abstract: Background: Leptomeningeal disease (LMD) is a devastating complication of advanced malignancy with a poor prognosis and limited therapeutic options. Whether immune checkpoint inhibitors (ICIs) alter disease course is unknown. Methods: We searched PubMed, EMBASE, Scopus, Cochrane, and clinicaltrials.gov according to PRISMA guidelines to analyze the therapeutic role and toxicity profiles of ICIs in the management of LMD. Studies reporting clinical outcome data of patients with LMD treated with ICIs were included. A comprehensive review of clinical characteristics and survival analysis was conducted. Results: We included 14 studies encompassing 61 patients. The median age at LMD diagnosis was 57 years (female=63.9%). Lung cancer (44.3%), breast cancer (27.9%), and melanoma (23.0%) were the most frequent primary tumors. Parenchymal brain metastases occurred in 37 patients, mostly treated with radiotherapy (83.3%). LMD most frequently presented with headache (42.1%) and was diagnosed by MRI findings (leptomeningeal T1-contrast enhancement: 96.7%) and/or positive cerebrospinal fluid cytology (86.5%). Patients received ICIs for a median duration of 7 months (range, 0.5–58.0): pembrolizumab (49.2%), nivolumab (32.8%), and/or ipilimumab (18.0%). The most common concurrent LMD treatments were radiotherapy (54.7%) and steroids (35.7%). Radiological responses at 6-months were complete (33.3%) and partial response (12.5%), stable disease (33.3%), and progression (20.8%). 22 patients developed ICI-related adverse events, mostly mild (100%) and uncommonly severe (15.6%). Median progression-free survival was 5.1 months, median overall survival was 6.3 months, and 12-month survival was 32.1%. Survival was correlated with ICIs (P=0.042), but not with primary tumors (P=0.144). Patients concurrently receiving steroids showed worse survival (P=0.040), with a median overall survival of 1.9 months. Conclusion: ICI therapy shows promise and appears to be well-tolerated in patients with LMD. Concurrent use of steroids is associated with worse survival. The role of ICIs in the multimodal management of LMD and their combination with steroids requires further analysis.